If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 29 = 7x + 9 Reorder the terms: 29 + 3x = 7x + 9 Reorder the terms: 29 + 3x = 9 + 7x Solving 29 + 3x = 9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 29 + 3x + -7x = 9 + 7x + -7x Combine like terms: 3x + -7x = -4x 29 + -4x = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 29 + -4x = 9 + 0 29 + -4x = 9 Add '-29' to each side of the equation. 29 + -29 + -4x = 9 + -29 Combine like terms: 29 + -29 = 0 0 + -4x = 9 + -29 -4x = 9 + -29 Combine like terms: 9 + -29 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| 3x+4=8x-18 | | 10+3(x-2)= | | 5x^2+4-125=0 | | x^3=95 | | 7x^2=112 | | 7(r-4)=3(r-4) | | s^2=-14-9s | | -12+3x=x-6 | | 3-5[5-(6y-5)]= | | 2(b-7)=4(b-5) | | 16-44=6(x-1)-4 | | d=h-64 | | 7*ex=14 | | 22w=15 | | 5(8m+8)=-6(8+8m) | | 3p(p+5)=0 | | 1-3m=1-7m | | 7ex=14 | | 2(x-4)+3x=12 | | 7x-(2x-4)=19 | | 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 |